Do You See What I See? Universal Translation, the Postmodernist Lens, and Implications for Educational Research - Jeffrey Hankey (Canadian Society for Studies in Education, 2018)
Abstract: In this philosophical paper, I make a case for the enduring utility of postmodernism as a lens through which to critique basic assumptions about knowledge and reality. I use this lens to tackle the contradictions built into so-called universal norms and values, which I argue are necessarily local and particular. This focus on the paradoxical structure of the universal informs my exploration of two related issues-the sense of practical paralysis, or inability to act, that seems to accompany postmodernism's incredulity toward universals, and the role of the ethical educational policy researcher, paralysis notwithstanding. Accordingly, I problematize universalist claims about principles of human resilience as well as access to formal education, with an eye to the indefinite suspension of truth-claims. I contend that educational policy researchers have a responsibility to actively engage with the tensions of philosophical problems and conclude by suggesting what sorts of ethical imperatives might be cultivated by a responsible educational policy researcher in working to reconcile the so-called truths of science and the doubts of postmodern philosophy.